Method for realizing detection of arsenic ions in different forms based on selective separation and chemical bonding effect

Through the selective separation of thiol cotton and the electrochemical enrichment of the modified Ti sheets of amino acid iron, combined with XRF technology, the problem of difficulty in detecting different forms of arsenic ions in the existing technology under mild conditions is solved, and efficient and economical arsenic ion detection is achieved.

CN119688753APending Publication Date: 2025-03-25Hefei Comprehensive Science Center Environmental Research Institute
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510078104.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-12-09
Filing Date
2025-01-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to detect different forms of arsenic ions quickly and sensitively under mild conditions, and often requires expensive large-scale instruments and professional operations.

Method used

A thiol cotton was used for selective separation, combined with Ti sheets modified with aminolated nanoferrooxide for electrochemical enrichment, and assisted X-ray fluorescence spectroscopy (XRF) to detect different forms of arsenic ions in water.

Benefits of technology

It realizes sensitive detection of different forms of arsenic ions, reduces detection costs, simplifies the operation process, and meets the WHO's detection requirements for trace arsenic in the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119688753A_ABST
    Figure CN119688753A_ABST
Patent Text Reader

Abstract

The invention discloses a method for realizing detection of arsenic ions in different forms based on selective separation and chemical bonding action. In the enrichment stage of the trivalent arsenic H3AsO3, adsorption of the sulfydryl cotton to the trivalent arsenic H3AsO3 is quantitatively analyzed through direct detection of XRF (X-Ray Fluorescence). In the enrichment stage of pentavalent arsenic ions H2AsO4 <->, aminated groups modified on the surfaces of the iron oxide nanosheets are protonated in a buffer solution under a weak acid condition to form NH3 < + >, the NH3 < + > and the pentavalent arsenic ions H2AsO4 <-> are subjected to the combined action of electrostatic attraction and chemical combination under the action of a positive electric field, and finally a sensitive XRF spectral signal is shown. The specific action mechanism of sensitive detection of arsenic ions in different forms in the work is explained by combining theoretical calculation. The research means of the electrochemical and spectrum combination method applied to rapid analysis of environmental pollutants is further enriched, and a new insight is provided for ion morphology analysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of analysis and detection, and specifically relates to a method for detecting arsenic ions in different forms based on selective separation and chemical bonding. Background Art

[0002] In addition to the common heavy metal ion pollution, the harm of heavy metal-like arsenic ions to the environment cannot be underestimated. It is well known that different forms of ions often correspond to different toxicity and physiological availability. Therefore, it is necessary to focus on the detection of morphological differentiation rather than the detection of the total amount of ions. At present, large-scale instrument detection methods such as atomic absorption spectroscopy and inductively coupled plasma mass spectrometry are still regarded as the mainstream analysis methods. This kind of precise detection often faces difficulties such as high cost and the need for well-trained professionals to operate, and is not conducive to on-site rapid analysis. As one of the classic means of ion analysis, electrochemical technology is often used for pollution monitoring in the environmental field, but in most cases, it needs to rely on precious metals and strong acid electrolytes, which is also a disadvantage that cannot be ignored. In addition, X-ray fluorescence spectroscopy (XRF) is also used for the detection and analysis of environmental pollutants, but it has the characteristics of insensitive detection limit and is often used for single form detection. Therefore, it is necessary to explore a method for sensitive detection of different forms of arsenic ions under mild conditions.

[0003] In addition, in existing research, there are no literature or patent reports on improving the detection limit of X-ray fluorescence spectroscopy through selective separation and bonding between specific atoms in functional materials and target ions, analyzing the specific mechanism of action from the perspectives of adsorption energy and DFT (density functional theory) bonding and orbital coupling, and applying it to the detection of arsenic in different forms. Summary of the invention

[0004] The purpose of the present invention is to provide a method for detecting arsenic ions in different forms based on selective separation and chemical bonding. The method of the present invention is a new method for detecting arsenic ions in different forms in water by assisting X-ray fluorescence spectroscopy (XRF) based on the mechanism of selective separation and bonding between functionalized nanomaterials and target ions. Specifically, the present invention is implemented by the following technical solutions:

[0005] A method for detecting arsenic ions in different forms based on selective separation and chemical bonding of the present invention comprises the following steps:

[0006] (1) Pre-separation of trivalent arsenic H3AsO3 and pentavalent arsenic H2AsO4 by adsorption of thiol cotton - In the test solution, trivalent arsenic H3AsO3 is selectively adsorbed and fixed on the surface of the thiol cotton, and trivalent arsenic H3AsO3 is quantitatively detected by XRF;

[0007] (2) The filtrate after adsorption by mercapto cotton is electrochemically enriched and then XRF is used to quantitatively detect pentavalent arsenic H2AsO4 - ; The electrochemical enrichment uses Ti sheets modified with amino nano-iron oxide as working electrodes.

[0008] The inventors found that the Ti sheet was selected after optimization and comparison. When other metals such as Al sheet were used, the background base was too large and the signal peak was not obvious. In addition, when a bare Ti sheet (without functional groups and nanomaterials) was used, it did not have enough active sites to interact with the ions to be measured, affecting the enrichment of the target ions on the electrode surface. If the titanium sheet was only modified with nano-iron oxide (without the synergistic effect of protonated amino groups), it would not have the effect of electrostatic attraction and hydrogen bonding. Only the Fe in Fe2O3 would interact with pentavalent arsenic H2AsO4 - The O in the amination forms an Fe-O bond, that is, the Ti sheet modified with NH2-Fe2O3 can construct an electrochemically sensitive interface and improve the electrochemical enrichment efficiency. The adsorption energy comparison results of the nano-iron oxide material for pentavalent arsenic before and after amination are shown in the figure. Figure 6 shown.

[0009] Furthermore, in the method of the present invention, the mercapto cotton in step (1) is preferably pre-moistened with a 4 M HCl solution, as acidic conditions are conducive to the adsorption of trivalent arsenic by the mercapto cotton.

[0010] Furthermore, in the method of the present invention, in order to achieve a better selective separation effect in step (1), the flow rate of the liquid flowing into the thiol cotton should be controlled, preferably not exceeding 2 mL / min.

[0011] Furthermore, in the method of the present invention, the preparation method of the amino nano iron oxide in step (2) is: take 20 mg Fe2O3 and dissolve it in a solution composed of 30 mL ethanol and 2 mL deionized water, then add 2 mL ammonia water and 200 μL APTMS (3-aminopropyltrimethoxysilane), ultrasonically treat for 2 h, shake at room temperature at 200 rpm for 2 h, then ultrasonically treat for 2 h, shake on a shaker at room temperature at 200 rpm for 2 h, centrifuge and wash with deionized water for multiple times, and vacuum dry at 60°C to obtain the amino nano iron oxide NH2-Fe2O3. The amino nano iron oxide NH2-Fe2O3 obtained by this method is a nanosheet structure, which can show better adsorption and catalytic properties in the present invention.

[0012] Furthermore, in the method of the present invention, in step (2), the Ti sheet modified with aminated nano-iron oxide is prepared by taking 20 μL of aminated nano-iron oxide liquid having a concentration of 1-4 mg / ml and uniformly dispersing it by ultrasonic oscillation, and evenly dropping it on the surface of the polished Ti sheet, and air-drying it. The inventors have found that a low concentration, such as less than 1 mg / ml, is not conducive to providing sufficient active sites, and a high concentration, such as more than 4 mg / ml, will result in the coverage of active sites, which is not conducive to obtaining a stable and reliable XRF signal. A concentration of 2-3 mg / ml is better, and a concentration of 2 mg / ml is the best.

[0013] Furthermore, in the method of the present invention, the electrochemical enrichment in step (2) is performed using the Ti sheet modified with amino nano-iron oxide as the working electrode, Ag / AgCl as the reference electrode, and Pt wire as the counter electrode. The filtrate after the adsorption of the thiol cotton is first neutralized with an alkali solution, and then the pH is adjusted to 6-6.5 with a HAc-NaAc buffer solution of pH=6 to be weakly acidic, the enrichment voltage is +1.5 V, and the enrichment time is 600s. Preferably, 4M NaOH is used to neutralize the 4M HCl used to wet the thiol cotton.

[0014] The inventors found that the positive electric field induces pentavalent arsenic H2AsO4 in the form of anions - Aggregated near the electrode, the Fe2O3 nanosheets and protonated amino-NH3 are uniformly dispersed + Modified Ti sheet (aminated nano-iron oxide modified Ti sheet), amino group is protonated under acidic conditions to form -NH3 + It is more conducive to the adsorption of pentavalent arsenic anions, the construction of electrochemical sensitive interface, and the improvement of electrochemical enrichment efficiency; pentavalent arsenic H2AsO4 in the test solution - It is fixed on the electrode surface under the combined action of positive electrosorption and chemical adsorption of electrode materials, and then quantitatively analyzed by XRF technology.

[0015] As a preferred technical solution, the method of the present invention for detecting arsenic ions in different forms based on selective separation and chemical bonding may include the following steps:

[0016] (1) Preparation of amino-containing nano-iron oxide:

[0017] Take 20 mg of Fe2O3 and dissolve it in a solution consisting of 30 mL of ethanol and 2 mL of deionized water, then add 2 mL of ammonia water and 200 μL of APTMS, ultrasonically treat for 2 h, oscillate at 200 rpm at room temperature for 2 h, then ultrasonically treat for 2 h, oscillate at 200 rpm at room temperature for 2 h; after washing with deionized water several times, amino-containing nano-iron oxide NH2-Fe2O3 was obtained;

[0018] (2) Amination of Ti sheets with nano-iron oxide modification:

[0019] Take 20 microliters of 2 mg / ml ultrasonically dispersed amino iron oxide liquid, evenly drop it on the polished Ti sheet surface, and air dry it;

[0020] (3) The test solution is controlled to flow into a syringe containing thiol cotton at a flow rate of no more than 2 mL / min, and trivalent arsenic H3AsO3 is selectively adsorbed and fixed on the surface of the thiol cotton, and the trivalent arsenic H3AsO3 is quantitatively detected by XRF; the thiol cotton is pre-soaked in 4M HCl solution for 5-10 minutes;

[0021] (4) Collect the filtrate after the mercapto cotton adsorption, and then perform XRF quantitative detection of pentavalent arsenic H2AsO4 after electrochemical enrichment. - The electrochemical enrichment conditions are as follows: the Ti sheet modified with amino nano-iron oxide is used as the working electrode, Ag / AgCl is used as the reference electrode, and the Pt wire is used as the counter electrode. The filtrate after adsorption by thiol cotton is first neutralized with alkali solution, and then the pH is adjusted to weak acidity with HAc-NaAc buffer solution (0.1M) of pH=6, the enrichment voltage is +1.5 V, and the enrichment time is 600 s.

[0022] The present invention pre-separates trivalent arsenic H3AsO3 and pentavalent arsenic H2AsO4 by specific adsorption of thiol cotton - In the mixed solution, trivalent arsenic H3AsO3 is selectively adsorbed and fixed on the surface of the thiol cotton for XRF quantitative detection. The filtered pentavalent arsenic H2AsO4 - After further electrochemical enrichment, the test was conducted. Specifically, the positive electric field induced pentavalent arsenic H2AsO4 in the form of anions. - Aggregated near the electrode, the Fe2O3 nanosheets and protonated amino-NH3 are uniformly dispersed + Modify the Ti sheet to construct an electrochemical sensitive interface and improve the electrochemical enrichment efficiency. Pentavalent arsenic H2AsO4 in the test solution - The positive adsorption and chemical adsorption of the electrode material are combined to fix it on the electrode surface, and then quantitatively analyzed by XRF technology. The results show that the thiol cotton and Fe2O3-NH3 used in the enrichment stage + The modified Ti sheet improved the detection limit of XRF and obtained a significant response signal. This method is effective for different forms of arsenic ions H3AsO3 and H2AsO4 -The detection has a good linear detection range, and the theoretical detection limit meets the 10 ppb requirement proposed by WHO (Environmental Science & Technology, 2019, 53(10): 5596-5604). Combined with the DFT theoretical calculation results, the selective separation mechanism of arsenic in different forms by mercapto cotton was revealed by using the significantly different adsorption energies, and the selective separation mechanism of arsenic in different forms by Fe and N atoms in functionalized nanomaterials was demonstrated from the perspective of orbital coupling. - The O atoms in the sample can form bonds (Fe-O bonds and N-O bonds), which greatly improves the enrichment effect of the target ions and thus improves the response signal of XRF, broadening the application prospects of X-ray fluorescence spectroscopy in the field of ion morphology.

[0023] The present invention proposes a new method for detecting the morphology of different forms of arsenic ions at the ppb level under the selective separation and chemical bonding. The selective separation of different forms of arsenic ions by thiol cotton is further explained by the difference in adsorption energy calculated theoretically. Trivalent arsenic H3AsO3 is enriched due to the specific adsorption of thiol cotton. After being wetted with HCl medium (studies have shown that thiol cotton soaked with 4M HCl has a better separation effect than 1M HCl), it has specific adsorption performance for trivalent arsenic when the flow rate is controlled to 2ml / min. The pentavalent arsenic ions H2AsO4 to be tested that are filtered out - Under certain conditions (using a certain concentration of NaOH solution to adjust the pH of the filtrate to a weakly acidic state, which is conducive to the protonation of the amino group), it is enriched through electrostatic adsorption and chemical bonding under the action of nanomaterials. The orbital coupling results of DFT calculations reveal the key role of chemical bonding between functionalized nanomaterials and target ions in sensitive detection. In the H3AsO3 enrichment stage, the adsorption of trivalent arsenic H3AsO3 by mercapto cotton was quantitatively analyzed by direct XRF detection. In the pentavalent arsenic ion H2AsO4 - In the enrichment stage, the amino groups modified on the surface of iron oxide nanosheets are protonated in a weakly acidic buffer solution to form NH3 + , with pentavalent arsenic ion H2AsO4 - Under the action of a positive electric field, electrostatic attraction and chemical bonding occur together, ultimately showing a sensitive XRF spectral signal. Combined with theoretical calculations, the specific mechanism of sensitive detection of arsenic ions in different forms in this work was explained. This further enriches the research methods of combining electrochemistry and spectroscopy for rapid analysis of environmental pollutants and provides new insights into ion form analysis.

[0024] According to the present invention, trivalent arsenic H3AsO3 and pentavalent arsenic H2AsO4 are carried out by using thiol cotton as a medium. -The selective separation of arsenic was carried out, and then the sensitive interface of the electrochemical enrichment stage was constructed with aminated ferric oxide. The sensitive detection of different forms of arsenic was achieved through the interaction between functional materials and target ions.

[0025] In this study, the separation of trivalent arsenic H3AsO3 and pentavalent arsenic H2AsO4 was achieved by using thiol cotton and functional material modified electrodes. - Selective enrichment of trivalent arsenic H3AsO3 is fixed on the surface of thiol cotton, while pentavalent arsenic H2AsO4 - It is not adsorbed and can be filtered out. H2AsO4 - Under the action of the positive electric field, the anions are further fixed on the electrode surface through electrostatic attraction and chemical bonding, which significantly improves the XRF detection performance and avoids the dependence on precious metals and strong acid electrolytes commonly used in electrochemical testing. The operation is simple, the cost is low, and there is no need to introduce precious metals, which has good potential application prospects. The core factor of high-sensitivity detection is the interaction between functional materials and target ions. The results show that the amino group protonates NH3 + With H2AsO4 - The combined effect of electrostatic adsorption and chemical bonding (Fe-O, NO) under a positive electric field is conducive to the improvement of XRF detection performance, and the applied positive electric field can avoid the interference of common cations (such as copper ions) due to electrostatic repulsion. In addition, the ferric oxide substrate with good conductivity helps to improve the electrical enrichment performance, which enables the XRF method to detect arsenic in different forms. As a result, the present invention effectively improves the detection sensitivity of arsenic under the chemical effect produced by the modification of nanomaterials and the action of the electric field control system. The present invention provides a new idea for reference for the differentiated detection of ions in different forms. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 (a) SEM and (b) TEM images of the prepared amino-modified nano-iron oxide.

[0027] Figure 2 DFT adsorption configuration diagram (with adsorption energy) and experimental results of mutual selectivity. (a) Adsorption configuration and adsorption energy of mercapto cotton for H3AsO3; (b) Adsorption configuration and adsorption energy of mercapto cotton for H2AsO4 - (c) is the XRF detection result of mutual selectivity.

[0028] Figure 3 Figure 2 is the XRF signal response and linear fitting diagram. (a) XRF signal response and linear fitting diagram of mercapto cotton to H3AsO3, (b) NH3 + -Fe2O3 to H2AsO4 - XRF signal response diagram and linear fitting diagram.

[0029] Figure 4 NH3 prepared in the example + -Fe2O3 to H2AsO4 - Comparison of orbital couplings of corresponding atoms after adsorption.

[0030] Figure 5 This is the result of the anti-interference experiment.

[0031] Figure 6 Fe2O3 and NH2-Fe2O3 were used as sensitive materials to detect H2AsO4 at different voltages. - The comparison of adsorption energy shows that the material modified by amino has lower adsorption energy for target ions than the original substrate, indicating that the adsorption configuration under this condition is more stable, that is, NH2-Fe2O3 is more conducive to the adsorption of H2AsO4 - interaction. DETAILED DESCRIPTION

[0032] The following embodiments are further descriptions of the content of the present invention as an explanation of the technical content of the present invention, but the essential content of the present invention is not limited to the following embodiments. Ordinary technicians in this field can and should know that any simple changes or replacements based on the essential spirit of the present invention should fall within the scope of protection required by the present invention.

[0033] Example 1

[0034] The test solution containing trivalent arsenic and pentavalent arsenic was prepared with HAc-NaAc buffer solution at pH=6. The test solution was passed from the syringe barrel through the thiol cotton pre-soaked with 4M HCl at a flow rate of no more than 2 ml / min under the action of the flow control valve. The thiol cotton adsorbed the target ions and was freeze-dried and pressed into a sheet for XRF testing. The obtained signal was marked as the XRF spectrum signal of trivalent arsenic. The filtrate was neutralized with 4 M NaOH solution, and the pH of the test solution was adjusted to weak acidity with HAc-NaAc buffer solution at pH=6 as electrolyte. The Ti sheet modified with aminated nano-iron oxide NH2-Fe2O3 was used as the working electrode, Ag / AgCl was used as the reference electrode, and Pt wire was used as the counter electrode. After electrochemical enrichment at a positive voltage of 1.5 V, the Ti sheet was placed under the XRF detector for testing. The obtained signal was the XRF spectrum signal of pentavalent arsenic. The preparation process of the materials involved, amination nano-iron oxide NH2-Fe2O3, is as follows: First, Fe2O3 (20 mg) is dissolved in ethanol (30 mL) and deionized water (2 mL), and ammonia (2 mL) and APTMS (200 μL) are added, and ultrasonic treatment for 2 h is performed alternately with shaking at room temperature (200 rpm) for 2 h. After washing with deionized water several times, NH2-Fe2O3 is obtained. Figure 1The SEM and TEM images of the amino-type nano-iron oxide prepared in Example 1 are given. It can be seen that the material is a uniformly dispersed hexagonal nanosheet structure, and there is no obvious agglomeration phenomenon.

[0035] The introduction of mercapto cotton is beneficial to the - Selective separation. Figure 2 The adsorption configuration and adsorption energy of arsenic ions in different forms on SC are compared, as well as the XRF test results of mutual selectivity. - The As and OH / O in the sample were used as sites for adsorption tests with mercapto cotton, and it was found that the adsorption of trivalent arsenic H3AsO3 was significantly stronger than that of pentavalent arsenic H2AsO4. - , and pentavalent arsenic H2AsO4 - The adsorption energy higher than 2eV can be considered that the substrate thiol cotton has no adsorption effect on the molecule, indicating that the thiol cotton has selectivity for H3AsO3. Figure 2 a is the adsorption of H3AsO3 by mercapto cotton, Figure 2 b is the mercapto cotton to H2AsO4 - adsorption. Figure 2 c is the comparison result of a single solution and a mixed solution; among them, the signal H3AsO3 shows the result of XRF test of the test solution of trivalent arsenic H3AsO3 after adsorption by thiol cotton, and the signal H3AsO3+ H2AsO4 - The XRF test result of the mixed solution of trivalent arsenic and pentavalent arsenic after adsorption by mercapto cotton. The signal H2AsO4 - Pentavalent arsenic H2AsO4 - The test solution was filtered out through the mercapto quilt and then electrochemically enriched with ammoniated iron oxide as the working electrode. The XRF test result showed that the signal H2AsO4 - +H3AsO3 is the result of XRF testing after pentavalent arsenic and trivalent arsenic mixed solution was filtered out by mercapto quilt and electrochemically enriched with ammoniated iron oxide as the working electrode. - The difference with the signal H3AsO3 is not big, which indicates that the mercapto cotton selectively adsorbs trivalent arsenic, while pentavalent arsenic is not adsorbed and will not be fixed on the surface of mercapto cotton, so the addition of pentavalent arsenic will not cause signal change. On the other hand, the signal H2AsO4 - +H3AsO3 and signal H2AsO4 - The difference is not big, because the trivalent arsenic in the mixed solution will be adsorbed by the thiol cotton, and the pentavalent arsenic will be filtered out, which further illustrates the selective adsorption of trivalent arsenic by the thiol cotton.

[0036] Using mercapto cotton and amino-containing nano-iron oxide materials as substrates, H3AsO3 and H2AsO4 were respectively detected by XRF method. - The results show that mercapto cotton can effectively adsorb H3AsO3, and protonated NH2-Fe2O3 can enrich H2AsO4 under electric field regulation and chemical bonding. - , Figure 3 The results for (a) H3AsO3 and (b) H2AsO4 are given. - Spectral detection signal diagram within a certain concentration range. - The theoretical detection limits are 9.2 ppb and 3.3 ppb, respectively, both meeting the WHO requirements for trace detection in the environment.

[0037] The adsorption configuration and DOS results of DFT reveal the mechanism of selective separation and chemical bonding, which further confirms the anti-interference performance of the substrate material for the detection of arsenic ions in different forms. Figure 4 The functionalized iron oxide and pentavalent arsenic ion H2AsO4 were given. - Orbital coupling before and after the action. It proves that the substrate material has a great influence on H2AsO4 - The adsorption is the combined effect of NO and Fe-O bonding.

[0038] Figure 5 For anti-interference experiment. Figure 5 a Based on 100 ppb H3AsO3 solution, add interfering ions SO4 2- 、NO3 - , Cu 2+ , Pb 2+ Etc., 4 M HCl can remove most of the interfering ions that affect the adsorption of thiol cotton (desorption), so the interference is within an acceptable range. Figure 5 b With 100 ppb H2AsO4 - As the base solution, add the interfering ion SO4 2- 、NO3 - , Cu 2+ , Pb 2+ etc., found H2AsO4 - The electric field applied during the detection process can effectively inhibit the aggregation of cations and is less interfered by anions. - The signal interference was not significant, and the signal difference was less than 15% compared with the detection signal without adding interference.

[0039] The base material of the present invention exhibits not only adsorption performance, but also enrichment detection under electric field regulation. The adsorption method can remove various heavy metal ions or arsenic ions, but the purpose of the present invention is not to remove them, but to achieve sensitive detection of different forms of arsenic through specific detection means. The present invention reveals a mechanism of selective separation and chemical bonding to achieve morphological differentiation detection, and finds that specific adsorption and chemical bonding between functional materials and target ions are key factors for sensitive detection. Combined with DFT theoretical calculations, the interaction mechanism between the ions to be tested and the functional materials is analyzed, and a morphological detection method of selective separation and chemical bonding is proposed, thereby achieving different forms of arsenic ions H3AsO3 and H2AsO4. - Selective detection.

[0040] It should be noted that the above-mentioned technical contents of the present invention are only for explanation and clarification to enable those skilled in the art to understand the technical essence of the present invention, so the technical contents are not used to limit the substantial protection scope of the present invention. The substantial protection scope of the present invention shall be subject to the claims. Those skilled in the art should know that any modification, equivalent substitution and improvement based on the substantial spirit of the present invention shall be within the substantial protection scope of the present invention.

Claims

1. A method for detecting arsenic ions in different forms based on selective separation and chemical bonding, comprising the following steps: (1) Pre-separation of trivalent arsenic H3AsO3 and pentavalent arsenic H2AsO4 by adsorption of thiol cotton - In the test solution, trivalent arsenic H3AsO3 is selectively adsorbed and fixed on the surface of the thiol cotton, and trivalent arsenic H3AsO3 is quantitatively detected by XRF; (2) The filtrate after adsorption by mercapto cotton is electrochemically enriched and then XRF is used to quantitatively detect pentavalent arsenic H2AsO4 - The electrochemical enrichment uses Ti sheets modified with amino-containing nano-iron oxide as working electrodes.

2. The method according to claim 1, characterized in that The thiol cotton in step (1) is pre-wetted with 4 M HCl solution.

3. The method according to claim 1, characterized in that Step (1) The test solution is flowed into a container containing thiol cotton at a flow rate not exceeding 2 mL / min.

4. The method according to claim 1, characterized in that The preparation method of the amino-type nano-iron oxide in step (2) is as follows: 20 mg of Fe2O3 is dissolved in a solution consisting of 30 mL of ethanol and 2 mL of deionized water, and then 2 mL of ammonia water and 200 μL of APTMS are added, followed by ultrasonic treatment for 2 h, shaking at room temperature at 200 rpm for 2 h, and then ultrasonic treatment for 2 h and shaking at room temperature at 200 rpm for 2 h; the mixture is washed with deionized water several times and dried to obtain the amino-type nano-iron oxide NH2-Fe2O3.

5. The method according to claim 1, characterized in that In step (2), the Ti sheet modified with amino nano-iron oxide is prepared by uniformly dropping an amino nano-iron oxide solution having a concentration of 1-4 mg / ml on the surface of the polished Ti sheet and air-drying the solution.

6. The method according to claim 1, characterized in that In step (2), the electrochemical enrichment was carried out using Ti sheet modified with amino-containing nano-iron oxide as the working electrode, Ag / AgCl as the reference electrode, and Pt wire as the counter electrode. The filtrate after adsorption by thiol cotton was first neutralized with alkaline solution, and then the pH was adjusted to weak acidity with HAc-NaAc buffer solution of pH=6. The enrichment voltage was +1.5 V and the enrichment time was 600 s.

7. The method according to any one of claims 1 to 6, characterized in that: The steps include: (1) Preparation of amino-containing nano-iron oxide: Take 20 mg of Fe2O3 and dissolve it in a solution consisting of 30 mL of ethanol and 2 mL of deionized water, then add 2 mL of ammonia water and 200 μL of APTMS, ultrasonically treat for 2 h, shake at 200 rpm at room temperature for 2 h, then ultrasonically treat for 2 h and shake at 200 rpm at room temperature for 2 h; wash with deionized water several times and dry to obtain amino-containing nano-iron oxide NH2-Fe2O3; (2) Amination of Ti sheets with nano-iron oxide modification: Take 20 microliters of 2 mg / ml amino nano-iron oxide liquid dispersed evenly by ultrasound, evenly drop it on the polished Ti sheet surface, and air dry it; (3) The test solution is controlled to flow into a syringe containing thiol cotton at a flow rate of no more than 2 mL / min, and trivalent arsenic H3AsO3 is selectively adsorbed and fixed on the surface of the thiol cotton, and the trivalent arsenic H3AsO3 is quantitatively detected by XRF; the thiol cotton is pre-soaked in 4M HCl solution for 5-10 minutes; (4) Collect the filtrate after the mercapto cotton adsorption, and then perform XRF quantitative detection of pentavalent arsenic H2AsO4 after electrochemical enrichment. - The electrochemical enrichment conditions are as follows: the Ti sheet modified with amino nano-iron oxide is used as the working electrode, Ag / AgCl is used as the reference electrode, and the Pt wire is used as the counter electrode. The filtrate after adsorption by thiol cotton is first neutralized with alkali solution, and then the pH is adjusted to weak acidity with HAc-NaAc buffer solution of pH=6. The enrichment voltage is +1.5 V, and the enrichment time is 600 s.